Multiple sites for double-strand breaks in whole meiotic chromosomes of Saccharomyces cerevisiae. - Zenvirth, D (1992)
We present a scheme for locating double-strand breaks (DSBs) in meiotic chromosomes of Saccharomyces cerevisiae, based on the separation of large DNA molecules by pulsed field gel electrophoresis. Using a rad50S mutant, in which DSBs are not processed, we show that DSBs are widely induced in S. cerevisiae chromosomes during meiosis. Some of the DSBs accumulate at certain preferred sites. We present general profiles of DSBs in chromosomes III, V, VI and VII. A map of the 12 preferred sites on chromosome III is presented. At least some of these sites correlate with known 'hot spots' for meiotic recombination. The data are discussed in view of current models of meiotic recombination and chromosome segregation.